2019
DOI: 10.1016/j.heliyon.2019.e01120
|View full text |Cite
|
Sign up to set email alerts
|

Woody species diversity, population structure, and regeneration status in the Gra-Kahsu natural vegetation, southern Tigray of Ethiopia

Abstract: The study was conducted at Gra-Kahsu protected natural vegetation (PNV) and communal grazing land (CGL), in order to evaluate the conservation impact level. The diversity of plant species, population structure of woody species, and regeneration status were analysed from 62 quadrats, each with 20 m × 20 m for trees and 5 m × 5 m for shrubs, using systematic sampling methods. A total of 64 vascular plant species belonging to 52 genera and 37 families from PNV and 43 plant species belonging to 34 genera and 25 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 15 publications
10
58
3
Order By: Relevance
“…Basal area: The total basal area of Hirmi natural forest for plant species with DBH >2 cm was 14m 2 /ha. This result was higher than the study conducted in Grat-Kahsu (5.32 m 2 /ha; Atsbha et al 2019) and Taltalle woodland area (0.44 m 2 /ha; Lemessa 2009). However, it was smaller than the other dry woodland forest studied in Abobo-Gog forest (Gambella Regional State) (29.3 m 2/ ha; Bareke 2018) and the normal basal area value for virgin tropical forests in Africa is (23-37 m 2 /ha; Lamprecht 1989).…”
Section: Vegetation Structure Of Hirmi Forestcontrasting
confidence: 59%
See 1 more Smart Citation
“…Basal area: The total basal area of Hirmi natural forest for plant species with DBH >2 cm was 14m 2 /ha. This result was higher than the study conducted in Grat-Kahsu (5.32 m 2 /ha; Atsbha et al 2019) and Taltalle woodland area (0.44 m 2 /ha; Lemessa 2009). However, it was smaller than the other dry woodland forest studied in Abobo-Gog forest (Gambella Regional State) (29.3 m 2/ ha; Bareke 2018) and the normal basal area value for virgin tropical forests in Africa is (23-37 m 2 /ha; Lamprecht 1989).…”
Section: Vegetation Structure Of Hirmi Forestcontrasting
confidence: 59%
“…Grat-Kahsu 64 species (Atsbha et al 2019) but less than the study conducted in Benshangul Gumuz regional state with 1102 species (Awas 2007).…”
Section: And Inmentioning
confidence: 71%
“…Other scholars studies conducted in woodlands of Ethiopia also reported similar findings. For instance Eba and Lenjisa (2017) Tesfaye et al (2019) 5 species respectively in their study. In terms of species richness, the dominance of Fabaceae was reported from similar vegetation studies done by different scholars in the country such as Zerihun et al (2017) and Tesfaye et al (2019).…”
Section: Woody Species Composition Of the Forestmentioning
confidence: 77%
“…For instance Eba and Lenjisa (2017) Tesfaye et al (2019) 5 species respectively in their study. In terms of species richness, the dominance of Fabaceae was reported from similar vegetation studies done by different scholars in the country such as Zerihun et al (2017) and Tesfaye et al (2019). The dominance of Fabaceae is also in line with the assessment results that show the dominance positions in the Flora of Ethiopia and Eritrea (Zerihun et al (2017).…”
Section: Woody Species Composition Of the Forestmentioning
confidence: 77%
“…A total of 48 woody species representing 23 families and 31 genera were recorded in the study area ( Figure 2). Present study revealed that Kara forest is floristically poor compared with other forest lands like Gra-Kahsu [18]. However, it is more or less comparable with Borana woodland [8] and better than Gambella low land [19], South Omo zone [3] and Benishangul-Gumuz [20] forests.…”
Section: Floristic Compositionmentioning
confidence: 89%